AUGMENTED REALITY FOR STUDENTS IN SOLAR SYSTEM SCIENCE SUBJECTS - Isa Faqihuddin Hanif; Restu Aji Prasetyo (JURNAL FASILKOM, 2024)
Technosa School is a private school founded by the Technosa Kusuma Bangsa Foundation. At Technosa School Middle School, especially in the solar system science subject, the teaching and learning process at the school is still carried out using auxiliary media in the form of video, but there are still signal and quota problems for students. Based on these problems, one of the Technosa School teachers stated that a new media was needed that was more flexible and could be used on students' smartphones considering that students at Technosa School already had smartphones. The method used in this research is the waterfall method. Based on the results of a questionnaire distributed to 31 respondents, an overall answer of 82.9% was obtained, the science learning application with the Augmented Reality feature can help students understand science material.